Timing dilemma: a systematic review and meta-analysis of short-term mortality in patients with COVID-19 undergoing tracheostomy with varied timing, including 7, 10 and 14 days - Beong Ki Kim; Hangseok Choi; Chi Young Kim (BMJ Open)
Objective To analyse the effects of tracheostomy timing on COVID-19 outcomes by comparing mortality rates at different time points (7, 10 and 14 days).Design Systematic review and meta-analysis.Data sources PubMed, Embase, Cochrane Library, Web of Science and Scopus were searched from 31 August 2023 to 6 September 2023.Primary and secondary outcomes measures The primary outcome was short-term mortality, defined as intensive care unit (ICU) mortality, hospital mortality and 28-day or 30-day mortality. The secondary outcomes included mechanical ventilation duration, ICU and hospital days.Results Among 3465 patients from 12 studies, the 10-day subgroup analysis revealed higher mortality for earlier tracheostomy than for later tracheostomy (49.7% vs 32.6%, OR 1.91, 95% CI 1.37–2.65). No significant differences were observed at 7- and 14-day marks. Earlier tracheostomy was associated with shorter mechanical ventilation (mean difference=−7.35 days, 95% CI −11.63 to −0.38) and ICU stays (mean difference=−11.24 days, 95% CI −18.50 to −3.97) compared with later tracheostomy. Regarding hospital stay, the later tracheostomy group exhibited a trend towards longer-term inpatients, with no significant difference.Conclusions No significant difference in short-term mortality was observed between patients undergoing tracheostomy at 7 and 14 days; however, at 10 days, later tracheostomy resulted in a lower mortality rate. Accordingly, subtle timing differences may impact short-term results in COVID-19 patients. Considering that the later tracheostomy group had longer mechanical ventilation and ICU stays, additional research is required to determine an optimal timing that reduces mortality cost-effectively.